1991
DOI: 10.2527/1991.691258x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of newborn Bos indicus and Bos indicus x Bos taurus calves after exposure to cold.

Abstract: Brahman (n = 9) and 1/2 Simmental x 1/4 Brahman x 1/4 Hereford (n = 11) calves were utilized to determine the influence of exposure to cold on the physiology of the neonate. All calves were removed from their dams within 20 min of birth and prior to suckling. Calves were assigned randomly within breed to either a warm (W; 31 degrees C) or cold (C; 4 degrees C) environmental treatment group. Jugular blood samples were collected via indwelling catheters at 20-min intervals for 180 min. At 100 to 120 min of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 4 publications
2
41
1
4
Order By: Relevance
“…Glucocorticoids are also essential for thermogenesis, and a marked increase in glucocorticoid concentrations has been reported in response to exposure to cold in neonatal calves [29]. It is most likely that glucocorticoides play an indirect role in supporting cold thermogeneisis through mobilization of lipids and glycogen to supply energy thermogenesis [30].…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids are also essential for thermogenesis, and a marked increase in glucocorticoid concentrations has been reported in response to exposure to cold in neonatal calves [29]. It is most likely that glucocorticoides play an indirect role in supporting cold thermogeneisis through mobilization of lipids and glycogen to supply energy thermogenesis [30].…”
Section: Introductionmentioning
confidence: 99%
“…The increased level of cortisol in calves of G 1 might be due to increase in lipolysis and utilization of brown adipose tissue for heat production. Godfrey et al (1991) also observed significantly (P<0.05) higher values of cortisol in Brahman calves after their exposure to cold. Maurya et al (2013) also reported significantly (P<0.05) higher values of cortisol in cold stressed lambs as compared to protected lambs.…”
Section: Cortisolmentioning
confidence: 60%
“…Um dos índices de eficiência reprodutiva mais importantes e utilizados na pecuária de corte é representado pela razão entre o número de bezerros produzidos pelo número de matrizes prenhes na estação de monta (Godfrey et al, 1991). Entre os fatores que podem afetar este índice, destaca-se a morte de bezerros no período perinatal.…”
Section: Introductionunclassified
“…Nesse contexto, a dificuldade dos bezerros em adaptar às condições ambientais adversas, como frio, flutuações de temperatura, vento e alta precipitação, têm especial relevância (Diesch et al, 2004;Godfrey et al, 1991).…”
Section: Introductionunclassified
See 1 more Smart Citation